Live attenuated Salmonella enterica serovar Choleraesuis vector delivering a conserved surface protein enolase induces high and broad protection against Streptococcus suis serotypes 2, 7, and 9 in mice. Issue 44 (14th October 2020) - Li, Quan; Lv, Yifan; Li, Yu-an; Du, Yuanzhao; Guo, Weiwei; Chu, Dianfeng; Wang, Xiaobo; Wang, Shifeng; Shi, Huoying
Abstract: Streptococcus suis, a major zoonotic pathogen in swine, can be classified into 35 serotypes. However, no universal vaccine against the multiple serotypes of S. suis is available, though some studies have shown homologous protection. Hence, developing an effective universal vaccine to protect pigs against multiple S. suis serotypes is necessary, or at the very least, to protect pigs against diseases caused by the dominant pathogenic serotypes. Enolase, a highly conserved surface protein, is present in all of the described S. suis serotypes. rSC0016 is an improved recombinant attenuated S. Choleraesuis vaccine vector, combining a sopB mutation with regulated delayed systems, achieving an adequate balance between host safety and immunogenicity. In order to develop a universal vaccine against the multiple serotypes of S. suis, a novel recombinant vaccine strain rSC0016 that carries a heterologous antigen enolase was developed in this study. According, it was found that the recombinant vaccine strain rSC0016(pS-Enolase) exhibited better colonization compared to the vaccine control strain rSC0018(pYA3493). In addition, a mouse model immunized with the strain rSC0016(pS-Enolase) elicited significant IgG antibody responses against both enolase and Salmonella antigens, while inducing good mucosal, humoral, and cellular immune responses against enolase. Finally, immunization with rSC0016(pS-Enolase) was shown to confer 100%, 80%, and 100% protection against the serotypes of SS2, SS7, and SS9, respectively, and significantly reduced histopathological lesions in mice. Overall, this study provides a promising universal vaccine candidate for use against the multiple serotypes of S. suis .